(untitled) (Studia austriaca, 2014)
In Tod des Tizian (1892) the painted image and its verbal evocation carry out an important function of poetics. In this verse play, Titian’s last painting offers a new representation perspective, which to a certain extent invalidates his previous production. Hofmannsthal here deals with a theme deeply rooted in his aesthetic program. The impulse towards a form supported by a sort of reciprocal strengthening of life and art takes on an eminently ethic configuration in which the aesthetic individual rediscovers his specific duty.